Selective laser melting porous metallic implants with immobilized silver nanoparticles kill and prevent biofilm formation by methicillin-resistant Staphylococcus aureus. (September 2017) - van Hengel, Ingmar A.J.; Riool, Martijn; Fratila-Apachitei, Lidy E.; Witte-Bouma, Janneke; Farrell, Eric; Zadpoor, Amir A.; Zaat, Sebastian A.J.; Apachitei, Iulian
Abstract: Implant-associated infection and limited longevity are two major challenges that orthopedic devices need to simultaneously address. Additively manufactured porous implants have recently shown tremendous promise in improving bone regeneration and osseointegration, but, as any conventional implant, are threatened by infection. In this study, we therefore used rational design and additive manufacturing in the form of selective laser melting (SLM) to fabricate porous titanium implants with interconnected pores, resulting in a 3.75 times larger surface area than corresponding solid implants. The SLM implants were biofunctionalized by embedding silver nanoparticles in an oxide surface layer grown using plasma electrolytic oxidation (PEO) in Ca/P-based electrolytes. The PEO layer of the SLM implants released silver ions for at least 28 days. X-ray diffraction analysis detected hydroxyapatite on the SLM PEO implants but not on the corresponding solid implants. In vitro and ex vivo assays showed strong antimicrobial activity of these novel SLM PEO silver-releasing implants, without any signs of cytotoxicity. The rationally designed SLM porous implants outperformed solid implants with similar dimensions undergoing the same biofunctionalization treatment. This included four times larger amount of released silver ions, two times larger zone of inhibition, and one additional order of magnitude of reduction in numbers of CFU in an ex vivo mouse infection model.